Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Step-by-step explanation:
Let the given ratio be pk : qk .
So , here the quadratic equation is lx² + nx + n = 0. With respect to Standard form ax² + bx + c = 0.
We have ,
- a = l
- b = n
- c = n
→ Sum of roots = -b/a = -n/l = qk + pk
→ Product of roots = c/a = n/l = k²pq .
[tex]=> \dfrac{n}{l} = \dfrac{k^2}{pq} \\\\=> k^2 =\dfrac{n}{pql} [/tex]
And here pk and qk is a root of the quadratic equation ,
[tex]=> lx^2 + nx + n = 0 \\\\=> l(pk)^2 + n(pk) + n = 0\\\\=> lp^2k^2+npk + n = 0 \\\\=> lp^2\bigg( \dfrac{n}{pql} \bigg) + np\bigg(\sqrt{\dfrac{n}{pql}} \bigg) + n = 0 \\\\ => n\bigg\{\dfrac{p}{q}+\sqrt{\dfrac{np}{lq}}+1\bigg\} = 0 \\\\=> \dfrac{p}{q}+\sqrt{\dfrac{np}{lq}}+1 =0\\\\=>\sqrt{\dfrac{p}{q}} \bigg( \dfrac{q}{p}+\sqrt{\dfrac{np}{lq}}+1\bigg) = 0 \\\\=> \sqrt{\dfrac{p}{q}}+ \sqrt{\dfrac{q}{p}}+ \sqrt{\dfrac{n}{l}}=0 \\\\\boxed{\red{\bf\longmapsto \sqrt{\dfrac{p}{q}}+ \sqrt{\dfrac{q}{p}} = - \sqrt{\dfrac{n}{l}}}} [/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.